Cover Image. Issue 12 (17th July 2019) - Unknown
Abstract : Cover Illustrations: A queen of the Spanish desert ant Cataglyphis velox surrounded by its worker offsrping. In this issue, Darras et al. study the distribution of social hybridogenesis in Spanish Cataglyphis . In hybridogenetic populations, queens mate with males originating from a different lineage to produce workers and use asexual reproduction to produce new reproductive individuals. Photo Credit: Hugo Darras